Fiji : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Fiji. (IMF Staff Country Reports; Country Report ;, 2010)
This 2009 Article IV Consultation highlights that Fiji's growth has been sluggish in recent years because of delays in economic reforms, worsening terms of trade, and political developments that have strained Fiji's international relations and hurt business confidence. Fiji's economy is expected to have contracted by 2 1\2 percent in 2009, reflecting the adverse impact of the global crisis on exports and tourism. Recent developments have put considerable pressure on the budget. Executive Directors have supported a tight monetary policy to ensure that inflation returns to low levels and to protect foreign exchange reserves.